PENGARUH RISK TAKING DAN FREE CASH FLOW TERHADAP PEMBAGIAN DEVIDEN: (STUDI EMPIRIS PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016) - Indrayani, Indrayani; Aprina, Aprina (Department of Accounting, Faculty of Economics & Business, 2017)
This study aimed to determine the effect of Risk Taking and Free Cash Flow on Dividend Payout. The number of samples used in this study was 39 observations at Commercial Banks listed on the Indonesia Stock Exchange (BEI) in 2014-2016. The sample was taken by using purposive sampling technique. The method of data analysis used in this research was multiple linear regression analysis. The result of research partially showed that Risk taking had a negative and significant effect on dividend payout and Free Cash Flow had a positive and significant effect on dividend payout. Simultaneously, Risk Taking and Free Cash Flow had a significant effect on dividend payout.